Gorham’s: Vanishing bone disease of arm (Indian Journal of Case Reports, 2020)
Vanishing bone disease is a rare disorder of the musculoskeletal system reported first in 1938 by Jackson and later described by Gorham and Stout. Since then, about 200 cases of this disorder have been reported. Much research has been done regarding etiopathogenesis, yet no conclusive evidence exists regarding the single best treatment modality. We present the case of a 55-year-old female with complaints of pain and swelling of the left arm and a history of trauma 1 year ago, for which she underwent open reduction and internal fixation. The pain and swelling persisted on follow-up. She had progressive osteolysis as well as the absence of osteoblastic reaction on imaging. After histopathological diagnosis, the patient started bisphosphonate, calcium, and Vitamin D3, but in view of severe pain and high proliferative index, she was treated with radiotherapy to the left arm. The case is being reported for its rarity and scarcity in the literature for defined treatment.